PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 155 PEKANBARU - Silvia Ridhuani; Erlisnawati Erlisnawati; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakProblem in this research is the low social sciences student achievement of Fifth graderes at SDN 155 Pekanbaru. It is needs to be improved to increase student learning achievement. Improvement efforts was conducted by applying the model of Student Teams Achievement Divisions (STAD) type Cooperative Learning. This research is classroom action research. Research was conducted on fifth graderes students at SDN 155 Pekanbaru academic year 2013/2014. Time of research was conducted on 1 April until 2 May 2013. Subject of research is fifth graderes students at SDN 155 pekanbaru, which contain of thirty students. They are 18 boys and 12 girls. Data collection techniques were used observation and test. Data analyzing techniques were used learning achievement, completeness individual and classical, teacher and student activity, group reward. Result of research showed that average of student basic score is 67.66. This increased in the first daily test on first cycle becomes 73.83. So improving student learning achievement from the base score to the first cycle is 9.11%. The second daily activity on second cycle average students learning achievement is 78.66. It increased from the base score to the second cycle about 16.25%. The third daily activity on third cycle average students learning achievement is 91.83. It increased from the base score to the third cycle about 35.72%. Percentage of classical completeness before classroom action research is 33.33% (not achieved). Percentage of classical completeness after first cycle is 66.66% (not achieved). In the second cycle increased to 80% (achieved). In the third cycle become 96.66% (achieved). From the explanation above show that application of the model of Cooperative Learning Student Teams Achievement Divisions (STAD) type cooperatif learning can improve student achievement in social science on fifth graderes students at SDN 155 Pekanbaru.Keyword: Cooperative Learning type Student Teams Achievement Divisions (STAD), Social science student Achievement.